Design informed driving innovation with evidence-based design - Brandt, Robert M., 1948-; Chong, Gordon H.; Martin, W. Mike.; Safari eBooks (Hoboken, N.J. : John Wiley & Sons, 2010)
"This practical, accessible book--for design professionals and students alike--is about design excellence and how to achieve it. The authors propose an evidence-based design approach that builds on design ingenuity with the use of research in ways that enhance opportunities to innovate. They show the power of research data to both reveal new design opportunities and convince stakeholders of the value of extraordinary work. A guide for all designers who want to earn their place as their clients' trusted advisor and who aspire to create places of beauty and purpose."--Resource description page.
Description based on print version record.
"The American Institute of Architects."
Includes bibliographical references and index.
Keywords: Evidence-based design; Electronic books